2012
DOI: 10.5194/tcd-6-5037-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ikaite crystal distribution in Arctic winter sea ice and implications for CO<sub>2</sub> system dynamics

Abstract: The precipitation of ikaite (CaCO3·6H2O) in polar sea ice is critical to the efficiency of the sea ice-driven carbon pump and potentially important to the global carbon cycle, yet the spatial and temporal occurrence of ikaite within the ice is poorly known. We report unique observations of ikaite in unmelted ice and vertical profiles of ikaite abundance and concentration in sea ice for the crucial season of winter. Ice was examined from two locations: a 1 m thick land-fast ice site an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 44 publications
2
28
1
Order By: Relevance
“…Finally, the simulated ikaite concentrations, up to 210 mmol m 23 , are in good agreement with the literature [Dieckmann et al, 2008[Dieckmann et al, , 2010Fischer et al, 2013;Geilfus et al, 2013;Rysgaard et al, 2012Rysgaard et al, , 2013, although they underestimate the largest values reported [e.g., Rysgaard et al, 2013Rysgaard et al, , 2014. Despite this general agreement, there are other unaccounted contributors to CaCO 3 precipitation or dissolution (ionic strength, temperature, and ionic inhibitors such as orthophosphate), which were not considered here and could be important in different environments [Papadimitriou et al, 2014].…”
Section: Ikaite Precipitation/dissolution and The Ta/dic Ratiosupporting
confidence: 74%
See 3 more Smart Citations
“…Finally, the simulated ikaite concentrations, up to 210 mmol m 23 , are in good agreement with the literature [Dieckmann et al, 2008[Dieckmann et al, , 2010Fischer et al, 2013;Geilfus et al, 2013;Rysgaard et al, 2012Rysgaard et al, , 2013, although they underestimate the largest values reported [e.g., Rysgaard et al, 2013Rysgaard et al, , 2014. Despite this general agreement, there are other unaccounted contributors to CaCO 3 precipitation or dissolution (ionic strength, temperature, and ionic inhibitors such as orthophosphate), which were not considered here and could be important in different environments [Papadimitriou et al, 2014].…”
Section: Ikaite Precipitation/dissolution and The Ta/dic Ratiosupporting
confidence: 74%
“…Field measurements of ikaite range from 15 to $900 mmol m 23 [Dieckmann et al, 2008[Dieckmann et al, , 2010Fischer et al, 2013;Geilfus et al, 2013;Rysgaard et al, 2012Rysgaard et al, , 2013]. In the model, the maximum ikaite concentration was limited, reaching an asymptotic maximum near 210 mmol m 23 when trying to increase calcification (i.e., when T CaCO3 is decreased, Figure 11b).…”
Section: Ikaite Precipitation/dissolution and The Ta/dic Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…Ikaite is a metastable mineral in the sedimentary realm formed naturally from aqueous solutions in near-freezing anoxic marine sediments (Zabel and Schulz, 2001;Greinert and Derkachev, 2004;Selleck et al, 2007). In recent years, a variety of different occurrences have been reported, including in high salinity and alkaline lakes (Last et al, 2013;Oehlerich et al, 2013) and polar sea ice (Dieckmann et al, 2008;Rysgaard et al, 2013). Both in nature and in the laboratory, ikaite readily crystallizes from solution at temperatures near 0°C , but rapidly decomposes into a mush of anhydrous CaCO 3 and water at warmer temperatures (Bischoff et al, 1993;Council and Bennett, 1993;Mikkelsen et al, 1999;Tang et al, 2009 -168, 2014 served at the same time in the sedimentary record (Larsen, 1994).…”
mentioning
confidence: 99%